Graft Copolymerization of N-Isopropylacrylamide and Acrylic Acid on Bentonite Colloids for In-Depth Fluid Diversion - Ahmed, A.A. (American Chemical Society, 2017)
A new cost-effective in-depth fluid diversion has been developed and reported. In this paper, the diverting agent is prepared successfully from natural bentonite particles that were modified with N-isopropylacrylamide (NIPAM) and acrylic acid (AA) copolymers. First, bentonite particles were intercalated with small precursor molecules that contained functional groups. These precursors were used to reduce the bentonite particle size and introduce a vinyl group for subsequent polymerization. Then, poly(NIPAM-co-AA) was grafted onto hydrophilic bentonite through a free radical polymerization process. The grafted bentonite morphology, microstructure, and thermal stability were investigated using FTIR spectroscopy, dynamic light scattering, XRD, and TGA measurements. The particle dispersion stability and rheological properties have been investigated by using a turbidimeter and rheometer. Sand packs and core flooding tests were conducted to investigate the injectivity and determine permeability reductions. Experimental results obtained revealed that the grafted bentonite was easily injected and gradually built flow resistance by particle straining and physical-chemical attachment. A significant permeability reduction fraction was observed when the diverting agent was injected into a brine saturated sand pack column. Increasing flow rate resulted in increasing pressure drop across the sand pack and a decrease in permeability reduction fraction. The results indicate that attached grafted bentonite particles deform by shear. Two-phase core flooding results show rock permeability reduced by 80 with an oil recovery increment of 12 after injecting grafted bentonite. These significant results highlighted new insights for successful applications of modified bentonite to improve reservoir conformance problems. © 2017 American Chemical Society.